Optimal Center of Rotation for Ball-And-Socket Thumb Carpometacarpal Arthroplasty Identified Using Three-Dimensional Kinematic Analysis: A Pilot Study - Murai, Atsuro; Kurosawa, Akihiro; Tada, Kaoru; Tachiya, Hiroshi; Tamai, Atsuya; Akahane, Mika; Matsuta, Masashi; Nakamura, Yuta; Kawashima, Hiroki; Tsuchiya, Hiroyuki (Frontiers in Bioengineering and Biotechnology, 2022)
Total joint arthroplasty is one of the surgical option for thumb carpometacarpal (CMC) joint arthritis, however the optimal position the center of rotation (COR) has not been quantified. The purpose of this study is to identify ideal ball-and-socket thumb carpometacarpal joint implants and the optimal position of the COR. We obtained eight right thumb computed tomography images each from ten healthy men, comprising four images each of thumbs at various angles of flexion-extension and abduction-adduction. We reconstructed 3D bone models on 3D CAD, created virtual ball-and-socket implants with three variables (neck offset, implant height, neck rotation), and found the optimal COR where the position change in the COR was smallest across various thumb positions. When the offset was 4.5 mm, neck rotation angle was 130.6° from the radial side to the palmar side of the first metacarpal, and implant height from the distal end of the metacarpal was 43.6 mm, we could restore almost normal kinematics. This study could serve as a reference for implant development and surgical technique guidelines.